2014
DOI: 10.1523/jneurosci.2654-13.2014
|View full text |Cite
|
Sign up to set email alerts
|

Theta and High-Frequency Activity Mark Spontaneous Recall of Episodic Memories

Abstract: Humans possess the remarkable ability to search their memory, allowing specific past episodes to be re-experienced spontaneously. Here, we administered a free recall test to 114 neurosurgical patients and used intracranial theta and high-frequency activity (HFA) to identify the spatiotemporal pattern of neural activity underlying spontaneous episodic retrieval. We found that retrieval evolved in three electrophysiological stages composed of: (1) early theta oscillations in the right temporal cortex, (2) increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
113
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 122 publications
(134 citation statements)
references
References 57 publications
19
113
1
1
Order By: Relevance
“…This approach was recently used to map the brain regions responsible for episodic memory encoding [27] and retrieval [4] during verbal free recall (modified in Figure 2A). During successful memory encoding, HFA could be separated into two spatiotemporal distinct stages: an early stage consisting of HFA increases along the ventral visual pathway culminating in hippocampal activation ( Early Encoding ; Figure 2A), and a late stage consisting of HFA increases in discrete areas of the left neocortex ( Late Encoding ; Figure 2A) [27].…”
Section: Synthesis: Hfa As a Functional Mapping Signalmentioning
confidence: 99%
See 3 more Smart Citations
“…This approach was recently used to map the brain regions responsible for episodic memory encoding [27] and retrieval [4] during verbal free recall (modified in Figure 2A). During successful memory encoding, HFA could be separated into two spatiotemporal distinct stages: an early stage consisting of HFA increases along the ventral visual pathway culminating in hippocampal activation ( Early Encoding ; Figure 2A), and a late stage consisting of HFA increases in discrete areas of the left neocortex ( Late Encoding ; Figure 2A) [27].…”
Section: Synthesis: Hfa As a Functional Mapping Signalmentioning
confidence: 99%
“…During successful memory encoding, HFA could be separated into two spatiotemporal distinct stages: an early stage consisting of HFA increases along the ventral visual pathway culminating in hippocampal activation ( Early Encoding ; Figure 2A), and a late stage consisting of HFA increases in discrete areas of the left neocortex ( Late Encoding ; Figure 2A) [27]. Episodic retrieval could be similarly staged into (1) early retrieval, consisting of a decrease in HFA in the right temporal cortex ( Early Retrieval ; Figure 2A), (2) late retrieval, consisting of an increase in HFA in the left neocortex and medial temporal lobe immediately before spontaneous recall ( Late Retrieval ; Figure 2A) and finally (3) motor/language activation during vocalization of the recalled item ( Response Production ; Figure 2A) [4]. Of note, theta oscillations (not shown) occurred simultaneously with decreases in HFA during early retrieval.…”
Section: Synthesis: Hfa As a Functional Mapping Signalmentioning
confidence: 99%
See 2 more Smart Citations
“…4 It is of importance to distinguish HFOs as distinct burstlike events in contrast to continuous HFO activity during cognitive processing that is locked to stimulus events. 4,13 The value of recording interictal spikes with electrocorticography as a biomarker to tailor resections has been disputed. 2 van 't Klooster et al confirmed that spikes are not a good biomarker for the epileptogenic zone, and their removal is not correlated with a good seizure outcome.…”
mentioning
confidence: 99%